The Impact of Celebrity Endorsement on Consumers' Behavioral Intention - Wu, You Li (2010)
The ever increasing product diversity and competition on the market of goods and services has dictated the pace of growth in the number of advertisement. Despite their admittedly diminished effectiveness over the recent years, advertisements remain the favored method of sales promotion. Consequently, advertisers have to explore every possible avenue of making an advertisement more noticeable, attractive and impellent for consumers. One way to achieve this is through invoking celebrity endorsements. Additionally, the use of a celebrity to endorse a product involves substantial costs; however, it does not immediately guarantee the success of an advertisement. The question of how celebrities can be used in advertising to the best advantage is therefore of utmost importance. Celebrity endorsements have become commonplace: empirical evidence indicates that approximately 25 per cent of advertisements feature some famous person as a product endorser. The popularity of celebrity endorsements demonstrates the relevance of the topic, especially in the context of the current global economic downturn, when companies are forced to save in order to survive, yet simultaneously to heavily invest in advertising and sales promotion. Therefore, the aim of this thesis is to examine what qualities (characteristics) of a celebrity endoser have an impact on the effectiveness of the advertisement in which he/she appears. 200 self-administered questionnaires were distributed in some area of Kuala Lumpur. The data collected from the survey were analyzed using SPSS software to measure the descriptive analysis, central tendency construct, reliability, factor analysis and multiple regressions. Consequently, the results of the analysis and the implications are discussed. Two experiments were conducted to test the hypotheses concerning the relationship between the celebrity endorsement and consumers' behavioral intention, ie source attractiveness, source credibility and the fit between the endoser and the endorsed product. Findings revealed that most of the factors are essentials in celebrity endorsement effectiveness apart from the congruity between the endorser and the product which is reported as insignificant. Lastly, this paper suggested that the usage of celebrity endorsement should be properly managed and planned as the appropriate selection of a celebrity will affect consumers' behavioral intention.